2010
DOI: 10.1007/s10194-010-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms related to efficacy and overuse of triptans in chronic migraine

Abstract: Migraine is a common type of headache and its most severe attacks are usually treated with triptans, the efficacy of which is extremely variable. Several SNPs in genes involved in metabolism and target mechanisms of triptans have been described. To define an association between genetic profile and triptan response, we classified a migrainous population on the basis of triptan response and characterized it for polymorphisms in the genes coding for monoamine oxidase A, G protein β3 and the cytochrome CYP1A2. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 15 publications
(16 reference statements)
1
38
0
Order By: Relevance
“…The feasible diagnostic setting for a tailored treatment of CM based on the application of pharmacogenomics will allow us to predetermine the efficacy of single old and new drugs by avoiding abuse and chronicization due to nonresponsivity of the abused drug [58].…”
Section: Pharmacogenomics and Chronic Migrainementioning
confidence: 99%
“…The feasible diagnostic setting for a tailored treatment of CM based on the application of pharmacogenomics will allow us to predetermine the efficacy of single old and new drugs by avoiding abuse and chronicization due to nonresponsivity of the abused drug [58].…”
Section: Pharmacogenomics and Chronic Migrainementioning
confidence: 99%
“…Gentile et al [39] showed that VNTR polymorphism in the MAOA gene is correlated with clinical response to triptans in patients with chronic migraine. However, we did not observe a difference in genomic distribution between consistent and inconsistent responders in migraine patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mean critical duration of overuse would be shortest for triptans (1.7 years), longer for ergotamine (2.7 years), and longest for simple analgesics (4.8 years) [10][11][12]. In Europe, MOH is rarely caused by overuse of opioids, employment of these compounds for symptomatic headache being largely discouraged in the medical environment [13].…”
Section: Introductionmentioning
confidence: 99%